ORTHOGNATHIC SURGERY EFFECT ON TEMPOROMANDIBULAR JOINT (TMJ PAIN AND TMJ SOUND): A SYSTEMATIC LITERATURE REVIEW - RUSDY, HENDRY; CHAIRUNNISA, RICCA; CIATAWI, SALIM (International Journal of Applied Pharmaceutics, 2025)
Dentofacial deformity refers to significant abnormalities in the alignment of the maxillomandibular complex, which can affect both the teeth's positioning within the arches and the relationship between the upper and lower jaws (occlusion). These deformities are more common in women (60.93%). Orthognathic surgery, which includes procedures like Le Fort I, Bilateral Sagittal Split Osteotomy (BSSO), and Intraoral Vertical Ramus Osteotomy (IVRO), is commonly performed to correct these deformities. However, the impact of such surgery on temporomandibular joint (TMJ) conditions remains still unclear. The purpose of this systematic review was to determine whether orthognathic surgery impact on temporomandibular joint (TMJ) conditions. Using the PICO framework, we conducted an extensive search of PubMed and Google Scholar for relevant studies published between 2015 and 2024. These studies assessed a total 859 abstracts, 10 studies met our inclusion criteria. Of these, 6 studies reported improvements in TMJ pain, and 7 studies reported improvements in TMJ sounds post-surgery. However, 2 studies noted a worsening of TMJ pain and 1 study observed worsened TMJ sounds. Additionally, 2 studies no improvement/stables in TMJ pain. Overall, while orthognathic surgery tends to improve TMJ conditions, there are instances where symptoms may worsen. Careful pre-surgical planning and patient selection are crucial to optimizing outcomes and minimizing the risk of adverse effects on TMJ health.